2013
DOI: 10.1021/jm400694d
|View full text |Cite
|
Sign up to set email alerts
|

Exquisite Selectivity for Human Toll-Like Receptor 8 in Substituted Furo[2,3-c]quinolines

Abstract: Toll-like receptor (TLR)-8 agonists activate adaptive immune responses by inducing robust production of T helper 1-polarizing cytokines, suggesting that TLR8-active compounds may be promising candidate adjuvants. We synthesized and evaluated hitherto unexplored furo[2,3-c]quinolines and its regioisomeric furo[3,2-c]quinolines, derived via a tandem, one-pot Sonogashira coupling and intramolecular 5 endo-dig cyclization strategy, in a panel of primary screens. We observed a pure TLR8 agonistic activity profile i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
67
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 63 publications
3
67
0
Order By: Relevance
“…In addition, several SAR studies indicated that the TLR8 activity was sensible to the length of C2-alkyl chain (8,9,11) and thus the hydrophobic centroid (H 4 ) of the C2-propyl of CL075 accounts different from the hydrophobic centroid (H 1 ) of other ligands were treated as two features. Usually, the effective pharmacophore models have 3-5 features; thus, we have limited our pharmacophore models to have 3-5 features only.…”
Section: Assessment Of Multiple Vs Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several SAR studies indicated that the TLR8 activity was sensible to the length of C2-alkyl chain (8,9,11) and thus the hydrophobic centroid (H 4 ) of the C2-propyl of CL075 accounts different from the hydrophobic centroid (H 1 ) of other ligands were treated as two features. Usually, the effective pharmacophore models have 3-5 features; thus, we have limited our pharmacophore models to have 3-5 features only.…”
Section: Assessment Of Multiple Vs Strategiesmentioning
confidence: 99%
“…To date, several synthetic small molecules have been identified as agonists of TLR8, leading to detailed structureactivity relationship (SAR) studies on these chemotypes including furo [2,3-c]pyridines, furo [2,3-c]quinolines, thiazolo [4,5-c]quinolines, 3-R-quinoline-2-amine, and C7-methoxycarbonylimidazoquines (8)(9)(10)(11). As yet, current experimental studies on TLR8 agonists are focused on limited chemotypes, and the information of TLR8 agonist binding has not been fully exploited.…”
mentioning
confidence: 99%
“…64 Thiazolo[4,5-c]quinoline modifications presented by David and coworkers demonstrate that alkyl chains at C2 of up to 3 carbons have increasing TLR8-agonistic potencies whereas alkylation of any kind at C4 was not tolerated (removed TLR8 agonistic potency entirely). 65 Furo[2,3-c]pyridines also showed TLR8 dependent NFκB signaling but failed to induce any proinflammatory cytokines. These compounds might be developed to lower the local or systemic reactogenicity (Figure 3).…”
Section: Introductionmentioning
confidence: 99%
“…Our discovery of the 2,3-diamino-furo[2,3- c ]pyridines 36 and 4-amino-furo[2,3- c ]quinolines, 32 leading to structure-based design of the 3-alkyl-quinoline-2-amines 28 as pure TLR8 agonists with no detectable TLR7 activity, was also motivated by observations that the strongly Th1-biasing TLR8 agonists could be useful as candidate vaccine adjuvants for the newborn. 53,54 Maternal immunoglobulins acquired by passive transplacental passage confer protection to the neonate for the first few weeks of life; 55 thereafter, the newborn is susceptible to a wide range of pathogens until early infancy.…”
Section: Introductionmentioning
confidence: 99%